OPPORTUNITIES AND PROBLEMS OF DIGITAL TECHNOLOGIES IN MODERN EDUCATION (Universal International Scientific Journal, 2026)
This article analyzes the importance of using digital technologies in the modern education system, their capabilities in the educational process, and existing problems. The formation of a digital educational environment, distance learning platforms, and the use of electronic resources are covered. The role of digital technologies in improving the quality of education and the problems associated with their effective use are also scientifically analyzed. At the end of the article, suggestions and recommendations are given for the development of digital technologies in the education system.
Keywords: digital technologies, modern education, distance learning, interactive methods, electronic educational resources, quality of education, innovative pedagogy, information and communication technologies.